2023
DOI: 10.3390/hematolrep15020024
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Thrombosis during and after a SARS-CoV-2 Infection: Pathogenesis, Diagnostic Approach, and Management

Abstract: Coronavirus disease 2019 (COVID-19) increases the risk of thromboembolic events, especially in patients with severe infections requiring intensive care and cardiorespiratory support. COVID-19 patients with thromboembolic complications have a higher risk of death, and if they survive, these complications are expected to negatively affect these patients’ quality of life. Moreover, recent data reported that the risk of thromboembolism remains high months after a COVID-19 infection. Therefore, understanding the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Notably, it has been suggested that COVID-19 infection can induce hypercoagulation, potentially contributing to pulmonary embolism, deep venous thrombosis, and the development of NBTE [7,8,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, it has been suggested that COVID-19 infection can induce hypercoagulation, potentially contributing to pulmonary embolism, deep venous thrombosis, and the development of NBTE [7,8,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, lung cancer stands out as the predominant cause of cancer-associated NBTE (Ca-NBTE) [3][4][5]. Recent studies have indicated a significant association between COVID-19 and infectioninduced hypercoagulation persisting up to 180 days after the initial infection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 can lead to increased expression of clotting factors and a simultaneous decrease in antithrombotic capabilities, which, combined with endothelial damage and vascular inflammation, creates favorable conditions for the formation of blood clots. These clots can subsequently block the coronary arteries, leading to a myocardial infarctions [26,27].…”
Section: Thrombosismentioning
confidence: 99%
“…Over the past few years, this problem has become even more acute. Thromboembolic disorders have become one of the most serious clinical manifestations of COVID-19, leading to complications of the disease, as well as increased mortality [ 3 , 4 ]. Moreover, the risk of blood clots remains high months after the illness.…”
Section: Introductionmentioning
confidence: 99%
“…C;1 H NMR (400 16. MHz, DMSO-d 6 ), δ (ppm): 0.75 (3H, s, C 6 -CH 3 ); 1.60 (3H, s, C 4 -CH 3 ); 1.69 (3H, s, C4 -CH 3 ); 2.11 (1H, d, J = 14.3 Hz, C 5 -H); 2.46 (1H, d, J = 14.4 Hz, C 5 -H); 3.81 (3H, s, CH 3 O), 6.75 (1H, s, C=CH); 7.14 (2H, d, J = 8.7 Hz, CHarom); 7.34 (2H, d, J = 8.8 Hz, CHarom); 7.48-7.51 (2H, m, CHarom); 13.34 (1H, br.s, NH). 13 C NMR, δ (ppm): 24.7, 24.7, 27.5, 30.0, 50.7, 52.5, 52.6, 53.9, 115.6, 115.6, 119.4, 119.5, 120.4, 126.8, 127.6, 128.2, 128.5, 130.2, 130.2, 130.9, 139.5, 141.9, 146.0, 146.3, 155.7, 165.8, 166.2, 167.4.…”
mentioning
confidence: 99%